Caracterização microestrutural, morfológica e óptica de filmes anódicos de ZrO2 - Strixino, Francisco Trivinho (2007)
In this work, we described some of the anodic ZrO2 properties such as microstructure, morphology and luminescence. The microstructural analysis during the breakdown process reveals that the oxide nature is similar to those oxides prepared by other methods. Nevertheless, a transition in the breakdown region is associated with the presence of crystallographic phases not stable at ambient temperature (tetragonal metastable phase). These results were explained in terms of changes in the crystallite size and microstructural of the oxide during the breakdown process. The morphology of the anodic oxides reveals a surface contained a high distribution of blisters structure. The adsorption of oxygen gas originated from the electrolysis of water modifies the oxide morphology at that spots location. A broad emission band between 350-600 nm is observed in ZrO2 films when excited at 325 nm. The origin and nature of this emission is proposed to be related to the existence of structure defects (F-centers and Zr3+ ions) inside the oxide generated during the breakdown process. Theories about the breakdown mechanism and the analyses of the Rapid Thermal Annealing and EPR data reinforced this proposition. The work was finalized with the production of anodic doped ZrO2 with Eu3+. The microstructural analysis reveals that these luminescent ions are located inside the oxide matrix and the anodic doping was explained in terms of the breakdown process.